Underinvestment in a Profitable Technology: The Case of Seasonal Migration in Bangladesh - Bryan, Gharad; Chowdhury, Shyamal; Mobarak, Ahmed Mushfiq (Econometrica, 2014)
Hunger during pre-harvest lean seasons is widespread in the agrarian areas of Asia and Sub-Saharan Africa. We randomly assign an $8.50 incentive to households in rural Bangladesh to out-migrate during the lean season. The incentive induces 22 % of households to send a seasonal migrant, their consumption at the origin increases significantly, and treated households are 8-10 percentage points more likely to re-migrate 1 and 3 years after the incentive is removed. These facts can be explained qualitatively by a model in which migration is risky, mitigating risk requires individual-specific learning, and some migrants are sufficiently close to subsistence such that failed migration is very costly. We document evidence consistent with this model using heterogeneity analysis and additional experimental variation, but calibrations with forward-looking households that can save up to migrate suggest that it is difficult for the model to quantitatively match the data. We conclude with extensions to the model that